Compound kushen injection in cancer treatments: Efficacy, active ingredients, and mechanisms - Yang Yang; Yu Lu; Tianduo Pei; Bao Guo; Jingquan Li; Hui Wang; Qian Ba (Elsevier, 2022)
Cancer remains a major cause of death and a severe threat to improve life span around the world. Although the cancer treatments have made great progress, the therapeutic outcomes of malignant tumors are limited due to drug resistance, side effect, and/or immunosuppressive tumor microenvironment. Traditional Chinese medicines (TCM) have been approved to be efficient against cancer. Compound kushen injection (CKI) is a typical approved TCM formula, with matrine, sophocarpine, oxymatrine, and oxysophocarpine as the top four bioactive ingredients. Due to the function of heat-clearing, dampness-expelling, detoxification, and analgesia, CKI has been widely used in the clinic for the treatment of cancer-induced pain and bleeding. Increasing studies have shown a broad-spectrum antineoplastic activity of CKI, especially combined with chemotherapy drugs. CKI significantly enhances the anti-cancer efficiency and reduces the side effect of chemotherapy drugs to improve the patient's quality of life. This review summarizes the anti-cancer effects and potential mechanisms of action of CKI and its active ingredients against liver cancer, lung cancer, breast cancer, esophageal cancer, gastric cancer, myeloid leukemia, and colon cancer, aiming to provide a comprehensive basis for exploring the clinical potency and application of CKI against cancer.